Analysis of regulatory and legislative acts on the conservation of the planet's biodiversity, ratified by Ukraine - Nagorniuk, Oksana; Mudrak, Oleksandr; Mudrak, Halyna; Sobczyk, Wiktoria (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The problems of studying, preservation and rational use of natural resources in modern conditions are no less relevant than the issues of politics and economics, and are absolutely connected with them. The analysis of regulatory and legislative acts on the conservation of the planet's biodiversity is made.
Keywords: normative-legal framework; biodiversity; sustainable development; stability of ecological systems